2011
DOI: 10.1016/j.tjog.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mifepristone combination with misoprostol and misoprostol alone in the management of intrauterine death

Abstract: Combination of mifepristone and misoprostol is more effective than the misoprostol alone for induction of labor in women with intrauterine death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
8
12
1
Order By: Relevance
“…Despite marked heterogeneity in terms of the study design and dose, the frequency of dosing and route of misoprostol, three previous studies of the induction of labor in IUFD showed significantly shorter IDI with the use of combined mifepristone and misoprostol, in comparison with the use of misoprostol alone, in line with our observations . In addition, Wagaarachchi et al ., in a retrospective analysis of a series of 96 consecutive cases, also found a comparable median IDI (8.5 h) using the combined regime …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Despite marked heterogeneity in terms of the study design and dose, the frequency of dosing and route of misoprostol, three previous studies of the induction of labor in IUFD showed significantly shorter IDI with the use of combined mifepristone and misoprostol, in comparison with the use of misoprostol alone, in line with our observations . In addition, Wagaarachchi et al ., in a retrospective analysis of a series of 96 consecutive cases, also found a comparable median IDI (8.5 h) using the combined regime …”
Section: Discussionsupporting
confidence: 91%
“…in a prospective study failed to show any significant difference in IDI among the groups receiving mifepristone and misoprostol versus misoprostol alone . The trials showing a favorable outcome with the combined regime used a higher and more frequent dose of misoprostol than the trials which failed to document such benefits . Fairly et al ., in a retrospective comparison between high and low dose misoprostol regimes after priming both groups with mifepristone, further established that the success of the combined regime depended on the dose of misoprostol …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations